The Use of C/N Ratio in Assessing the Influence of Land-Based Material in Coastal Water of South Sulawesi and Spermonde Archipelago, Indonesia - Nasir, Andriani; Lukman, Muhammad; Tuwo, Ambo; Hatta, Muhammad; Tambaru, Rahmadi; Nurfadilah, (Frontiers in Marine Science, 2016)
Measurement of C-N magnitude and C/N ratio from particulate matter is used to explain the source of terrestrial and sea particulates. Therefore, this study aimed at using C/N ratio in assessing land-based material in the west coast of Spermonde area, Indonesia on suspended matter. Samples of SPM were collected in two seasons (transition and dry seasons), in coastal waters of Tallo, Maros, and Pangkep estuaries. The results of research showed that Ctot was more abundant than was Ntot in particulates from river rather than from sea region, reflecting most of the terrestrial organic matter stored before meeting with sea. C/N ratio on the west coast of South Sulawesi was in the range of 7-19.7, showing that organic matter in Tallo estuary in transition season was dominantly autochthonous, while in dry season it was found to be dominantly terrigenous organic matter that gave an indication that land factor was significant in waste supply. The same thing was found in Maros estuary and Pangkep estuary in transition season and dry season; at all points of observation there were findings of particulates coming from terrigenous organic matter. Percentage of nutrient absorbed in particulate was low and could become a eutrophication stressor, where SPM found only ranged from 9.60 to 55.1 mgL-1 with maximum average in dry season and minimum in transition season. On the contrary, POM was maximum in transition season and minimum in dry season with dominant particulate organic matter source from the sea itself.